Influence of Leader-Member Exchange on Organizational Citizenship Behavior Mediated by Employee Engagement at The Regional Development Planning Agency Yogyakarta - Kartikasari, Evi Diana; Wahyuni, Purbudi (CV. Strata Persada Academia, 2025)
This study aims to determine the effect of leader member exchange on organizational citizenship behavior with employee engagement as a mediating variable at the Yogyakarta Special Region Regional Development Planning Agency in Yogyakarta. This type of research uses quantitative research. The data sources in this study used primary data and secondary data. The population in this study were 55 civil servant respondents of the Yogyakarta Special Region Development Planning Agency using the census technique. The analytical technique used is Structural Equation Model (SEM) Partial Least Square (PLS) method with SmartPLS 4 program. The results of this study state that leader member exchange directly has a positive and significant effect on organizational citizenship behavior, leader member exchange directly has a positive and significant effect on employee engagement, employee engagement directly has a positive and significant effect on organizational citizenship behavior, and leader member exchange has a positive and significant effect on organizational citizenship behavior through mediation of employee engagement.